Exploring Medicaid Dental Utilization in Kansas: Trends, Gaps, and Special Populations - Kothari, Isha (My University, 2025)
As part of my internship at Oral Health Kansas (OHK), I conducted a practice-based project focused on Medicaid dental service utilization among individuals with Intellectual and Developmental Disabilities and Autism Spectrum Disorder (IDD/autism). OHK’s mission is to improve oral health equity across Kansas, and under the guidance of the agency’s leadership, I gained valuable exposure to advocacy, policy translation, and data-driven public health practice. My project aimed to analyze Medicaid dental service use from 2022 to 2024, with a focus on disparities by age, geography, and waiver enrollment. To achieve this, I created an interactive dashboard that visualized enrollment patterns, procedure utilization, and provider distribution. The dashboard served as a systems-thinking tool, allowing stakeholders to see how factors such as geography, waiver type, and provider availability interacted to shape access. To translate these findings for diverse audiences, I developed two key products: an executive summary tailored for Kansans, policymakers, and providers, and a flyer designed for caregivers of individuals with IDD/autism. Both products used plain language, visuals, and accessible formatting to communicate complex data in audience-appropriate ways. These materials helped transform raw data into actionable insights that could guide advocacy, policy development, and community awareness. Through this experience, I strengthened my skills in interpreting quantitative data, applying health equity frameworks, and communicating findings across different sectors. The project demonstrated how practice-based research can inform real-world policy discussions, support coalition-building, and contribute to improving Medicaid dental access for vulnerable populations in Kansas.
Keywords: intellectual and developmental disabilities; autism spectrum disorder IDD/autism; Medicaid; dental utilization; Kansas